Meter-scale conditioned hydrodynamic optical-field-ionized plasma channels - Picksley, A; Alejo, A; Shalloo, RJ; Arran, C; von Boetticher, A; Corner, L; Holloway, JA; Jonnerby, J; Jakobsson, O; Thornton, C; Walczak, R; Hooker, SM (American Physical Society, 2020)
We demonstrate through experiments and numerical simulations that low-density, low-loss, meter-scale plasma channels can be generated by employing a conditioning laser pulse to ionize the neutral gas collar surrounding a hydrodynamic optical-field-ionized (HOFI) plasma channel. We use particle-in-cell simulations to show that the leading edge of the conditioning pulse ionizes the neutral gas collar to generate a deep, low-loss plasma channel which guides the bulk of the conditioning pulse itself as well as any subsequently injected pulses. In proof-of-principle experiments, we generate conditioned HOFI (CHOFI) waveguides with axial electron densities of ne0≈1×10^17cm−3 and a matched spot size of 26μm. The power attenuation length of these CHOFI channels was calculated to be Latt=(21±3)m, more than two orders of magnitude longer than achieved by HOFI channels. Hydrodynamic and particle-in-cell simulations demonstrate that meter-scale CHOFI waveguides with attenuation lengths exceeding 1 m could be generated with a total laser pulse energy of only 1.2 J per meter of channel. The properties of CHOFI channels are ideally suited to many applications in high-intensity light-matter interactions, including multi-GeV plasma accelerator stages operating at high pulse repetition rates.